Primary-user behavior based joint routing and channel allocation algorithm in cognitive radio networks - Jing LIU; Pin-yi REN; Shao-li XUE; Chao ZHANG (Tongxin xuebao)
To resolve the unstable routing problem due to the variation of spectrum availability caused by primary users’ behaviors in cognitive radio networks (CRN),a primary-user behavior based joint routing and channel allocation (PUB-JRCA) algorithm was proposed.The PUC-JRCA algorithm characterized the primary-user behavior by using the call-based model.According to the route discovery mechanism in the dynamic source routing protocol,the destination node selected the route which received the least impact from primary-user behaviors after receiving a number of route requests.Then,the destination sent back the route reply packet (RREP) along the selected route,and the channel allocation was performed when the RREP passed each node on this route.Theoretic analyses prove that the expected available transmission time for the packet delivery is inversely proportional to the probability that PU is active.Moreover,the computational complexity of the proposed algorithm is proportional to the number of nodes in the CRN.Simulation results show that the proposed algorithm has higher packet delivery ratio and lower average packet delay than the Gymkhana routing scheme.